Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.2174/1871526515666150320161440
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Value of Black Seed Oil in Methotrexate Hepatotoxicity in Egyptian Children with Acute Lymphoblastic Leukemia

Abstract: Black cumin seeds decreased MTX hepatotoxicity and improved survival in children with ALL and can be recommended as adjuvant drug in patients with ALL under methotrexate therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…In ALL, which is the most common childhood malignancy [108], increased numbers of lymphoblasts are present in the circulating blood and in different tissues and organs [48]. A study by Hagag et al reported that NS oil (80 mg/kg/day) administered for one week after each methotrexate treatment could reduce hepatotoxicity and improve the survival rate in ALL children undergoing that treatment [108]. Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ALL, which is the most common childhood malignancy [108], increased numbers of lymphoblasts are present in the circulating blood and in different tissues and organs [48]. A study by Hagag et al reported that NS oil (80 mg/kg/day) administered for one week after each methotrexate treatment could reduce hepatotoxicity and improve the survival rate in ALL children undergoing that treatment [108]. Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, herbal medicines, such as NS, can be useful alternatives; however, before such herbal medicines are used extensively, many RCTs should be conducted in order to evaluate and confirm the effects of herbal medicines [46, 48, 108]. One obvious example is sero-reversion in HIV-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…They were treated with methotrexate-based treatment protocol14–18 and delayed Ca leucovorin rescue according to methotrexate levels 19. Silymarin 420 mg/day, (In the form of Legalon- MEDA Pharma GmbH- tablets 140 mg per tablet one hour before each meal (3 times daily) or Hepaticum syrup (Medical Union Pharmaceuticals, Egypt) in case of inability to swallow the tablet form; (each 5 ml of Hepaticum contains 50 mg Silymarin) was added in 3 divided doses one hour before each meal for one week after each MTX dose 7,20…”
Section: Methodsmentioning
confidence: 99%
“…Nálunk 1991 után csak vírusinfekciókra szűrt vérkészítményeket használunk, egy betegünk sem fertőződött C-hepatitisvírussal a kezelés alatt. [11], feketeköménymag-kivonattal [12,13], silymarinnal [14], valamint ursodeoxycholsavval [15], amelyek biztonságosnak tűnnek, és nem befolyásolják a citosztatikumok metabolizmusát, hatását. Kedvezőtlen prognózist írtak le olyan toxikus májártalmakban, ahol a normálérték háromszorosát meghaladó ALT-érték a normálérték kétszeresét meghaladó összbilirubin-szinttel társul [16,17].…”
Section: Megbeszélésunclassified